Mounting Non-Performing Assets Of Indian Banks - Reasons, Impact And Role Of Arcil (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The presence of mounting Non Performing Assets in the  Indian banking system acts as a threat to their financial  performance in several ways. Due to its increasing number  earning assets in the financial sector decline even as  operating expenses increases. Management and financial  resources are diverted to Non Performing Assets problems  and away from more productive uses. Non Performing  Assets not only puts strain on the profitability on the banks  but also eroded their productivity and efficiency. The Non  Performing Assets are the bad debts and non recovered  loans of the banks which now stand at over 90,000 crores.  Large scale Non Performing Assets (NPA) when left  unattended, causes continued economic and financial  degradation. This results in credit crunch and generally  signals adverse investment climate. To resolve NPA problems and help restore the health and confidence of the  financial sector the Narshimham committee report (II) on  banking sector reforms recommended the establishment  of Asset Reconstruction Companies (ARC) and consequently, Asset Reconstruction Company Limited  (ARCIL), the pioneer Assets Reconstruction of India,  commenced its operation from August 29, 2003. This paper traces the various aspects like causes and  impact of increasing NPA of Indian Banks along with the  step forward taken by the ARCILin their restructuring.
Keywords: Non-Performing Assets; SRFAESI; Asset Reconstruction Company Limited ARCIL; Asset Reconstruction Companies (ARCs)